Model Pengelolaan Ekowisata Di Desa Beloi Pulau Atauro Timor-Leste - Isaura Pereira; I Made Adikampana (Program Studi Sarjana Pariwisata, Fakultas Pariwisata, Universitas Udayana, 2017)
The purpose of this article is to identify the management model of ecotourism in the village of Beloi. This research was conducted in the village of Beloi using survey method. Data collection is conducted in-depth interviews and observations to the respondents. Method of sampling is random with interviewees interviewed related parties among others, head of Atauro Island, village chief Beloi, representatives of local communities, and investors. The data collected is analyzed using the concept of ecotourism. These results indicate that the involvement of local communities in tourism activities in the village of Beloi still minimal. Ownership of tourism facilities which are dominated by the Government and investors because the local people can not feel the Beloi Village economic benefits. In addition Management Model of ecotourism in the village is still dominated by Government Beloi and investors. Local communities as the owners of the attraction still rarely involved in tourism activities. Keywords: Model, Ecotourism, Participation, Local Community